Profitability and Liquidity Impact on Dividend Payout Ratio: Evidence from Indonesian Consumer Goods Industry: Pengaruh Profitabilitas dan Likuiditas terhadap Rasio Pembayaran Dividen: Bukti dari Perusahaan Industri Barang Konsumsi di Indonesia - Siti Dwi Septiyani Rinatun; Drs. Nurasik, MM Nurasik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to examine the relationship between profitability and liquidity with the dividend payout ratio (DPR) in the Consumer Good Industry on the Indonesia Stock Exchange during the period of 2017-2019. The research employed purposive sampling, resulting in a sample of 45 companies over the three-year period. Using secondary data, the variables were analyzed using SPSS version 25 and tested using partial t-tests. The findings reveal that the DPR during 2017-2019 is positively influenced by the return on equity (ROE) and return on assets (ROA), as well as the current ratio (CR). However, the quick ratio (QR) was found to have no significant impact on the DPR. These results contribute to the understanding of the factors influencing dividend policy in the Consumer Good Industry, providing valuable insights for investors, managers, and policymakers. Highlights: Profitability and Liquidity: Explore the influence of profitability and liquidity on the dividend payout ratio in the Consumer Goods Industry of Indonesia. Dividend Payout Ratio: Investigate the relationship between financial performance indicators, such as ROE and ROA, and the distribution of dividends by companies. Consumer Goods Industry: Focus on companies operating in the Consumer Goods Industry listed on the Indonesia Stock Exchange and analyze their dividend policies. Keywords: Profitability, Liquidity, Dividend Payout Ratio, Consumer Goods Industry, Indonesia